2018
DOI: 10.1073/pnas.1808981115
|View full text |Cite
|
Sign up to set email alerts
|

Transcription initiation defines kinetoplast RNA boundaries

Abstract: Mitochondrial genomes are often transcribed into polycistronic RNAs punctuated by tRNAs whose excision defines mature RNA boundaries. Although kinetoplast DNA lacks tRNA genes, it is commonly held that in Trypanosoma brucei the monophosphorylated 5′ ends of functional molecules typify precursor partitioning by an unknown endonuclease. On the contrary, we demonstrate that individual mRNAs and rRNAs are independently synthesized as 3′-extended precursors. The transcription-defined 5′ terminus is converted into a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 42 publications
2
38
2
Order By: Relevance
“…and Serganov 2015). This would be consistent with analyses showing that mutation of MERS1 residues Glu257 and Glu258 to alanines impairs RNA processing in vivo (Sement et al 2018). However, studies have shown that it is challenging to definitively ascribe a residue as the catalytic base in Nudix hydrolases as substitution of many active site residues can either impair or abrogate binding (Piton et al 2013;Vasilyev and Serganov 2015).…”
Section: Biochemical Test Of Mers1-rna Structuresupporting
confidence: 83%
See 4 more Smart Citations
“…and Serganov 2015). This would be consistent with analyses showing that mutation of MERS1 residues Glu257 and Glu258 to alanines impairs RNA processing in vivo (Sement et al 2018). However, studies have shown that it is challenging to definitively ascribe a residue as the catalytic base in Nudix hydrolases as substitution of many active site residues can either impair or abrogate binding (Piton et al 2013;Vasilyev and Serganov 2015).…”
Section: Biochemical Test Of Mers1-rna Structuresupporting
confidence: 83%
“…Data indicate that MERS1 forms a complex with the MERS2 and MER3 proteins and that these interactions activate MERS1 activity (Sement et al 2018). The 946 residue MERS2 protein contains several pentatricopeptide (PPR) motifs, which are interaction motifs that may be involved in binding MERS1 and/or RNA.…”
Section: Mers1-helical Interactionmentioning
confidence: 99%
See 3 more Smart Citations